PERAN INIDIVIDUAL ENTREPRENEURIAL ORIENTATION DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP MANAJEMEN KONFLIK PADA KARYAWAN EVENT ORGANIZER DI SURABAYA - Jimmy Ellya Kurniawan (Psibernetika, 2021)
Event organizer or EO is a service company that is engaged in organizing events. Cooperation and communication are important values in work, but these two values often create conflicts. The conflict management solution-orientation is a management strategy that can provide the best solutions for EO companies. This study aims to look at the role of individual entrepreneurial orientation and organizational citizenship behavior in individual conflict management abilities. The respondents of this study were 114 event organizer employees in Surabaya. The results of the multiple linear regression test show that individual entrepreneurial orientation and organizational citizenship behavior have significant impact and contribute 48.6% on conflict management solution- orientation. The results show that individual entrepreneurial orientation has a bigger role than organizational citizenship behavior. Based on the results of these tests, it can be concluded that individual entrepreneurial orientation and organizational citizenship behavior together have a role in conflict management solution-orientation, but individual entrepreneurial orientation has a bigger role than organizational citizenship behavior on conflict management solution-orientation.